2021
DOI: 10.3390/ijerph18052702
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sedentary Time, Physical Activity, and Health-Related Quality of Life in Spanish Children

Abstract: Higher sedentary time and lower physical activity (PA) are associated with a poor health-related quality of life (HRQoL) in children. The aims of this study were: (1) to analyze the sedentary time, objectively measured PA levels (light, moderate, vigorous, and moderate-to-vigorous physical activity (MVPA)), and HRQoL dimensions (physical well-being, emotional well-being, self-esteem, family, friends, school, and total score) in children; and (2) to examine the association between sedentary time, PA levels, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
2
10
0
1
Order By: Relevance
“…Regarding physical activity intensity, three studies [ 32 , 33 ] showed that the strongest associations between satisfaction with life and physical activity were found in those adolescents who participated in vigorous physical activity. However, as previously found for the HRQoL [ 26 ], boys and girls differently responded to physical activity. In this regard, for boys, vigorous physical activity can be regarded as the predictor of better satisfaction with life, while, for girls, moderate-to-vigorous physical activity might be considered as a risk factor for lower life satisfaction [ 34 ].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Regarding physical activity intensity, three studies [ 32 , 33 ] showed that the strongest associations between satisfaction with life and physical activity were found in those adolescents who participated in vigorous physical activity. However, as previously found for the HRQoL [ 26 ], boys and girls differently responded to physical activity. In this regard, for boys, vigorous physical activity can be regarded as the predictor of better satisfaction with life, while, for girls, moderate-to-vigorous physical activity might be considered as a risk factor for lower life satisfaction [ 34 ].…”
Section: Introductionsupporting
confidence: 69%
“…In the same vein, a study that explore the commitment of physical activity recommendations found that meeting combinations of screen time with moderate-to-vigorous physical activity were related to higher HRQoL [ 25 ]. However, a previous study found that light intensity physical activity was associated with higher HRQoL in females whereas, in males, moderate and vigorous PA levels were associated with higher HRQoL values [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors that determine HRQoL in adolescents have been studied in numerous studies in recent years, most of them finding significant relationships with lifestyle habits: for example, quality of life in adolescence has been associated with physical activity and sedentary lifestyle [ 1 , 4 , 9 , 10 , 11 ] or eating habits [ 12 ]. Wu et al, for example, conducted a systematic review of cross-sectional and longitudinal studies on the subject and found evidence that a higher level of physical activity and less time spent in sedentary behavior are associated with higher HRQoL among the general population of children and adolescents [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, high levels of MVPA were observed in the present study. Although children are normally depicted with low PA levels in large, survey-based studies ( Hallal et al, 2012 ; Aubert et al, 2018 ; Guthold et al, 2020 ), research with accelerometry has also observed MVPA levels above 60 min per day among pediatric populations ( Camiletti-Moirón et al, 2020 ; Ávila-García et al, 2021 , Llorente-Cantarero et al, 2021 ; Padmapriya et al, 2021 ), which reflect the average recommended engagement in MVPA for children and adolescents according to the most recent World Health Organization guidelines and several international PA guidelines ( Chaput et al, 2020 ; Parrish et al, 2020 ). We believe this to be a positive finding, considering the many health benefits that result from maintaining high levels of PA ( Poitras et al, 2016 ; Chaput et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%